2007
DOI: 10.1098/rspb.2007.1585
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection mediated by the thermoregulatory effects of male colour pattern in the ambush bugPhymata americana

Abstract: Sexual dimorphism in coloration is a taxonomically widespread phenomenon often attributed to sexual selection on visual signals. However, the ambush bug Phymata americana exhibits sexual dimorphism in coloration that has no apparent signalling function. Here we provide evidence that colour pattern in this species influences male mating success indirectly through its effect on thermoregulation. We demonstrate, using experimental manipulation, that individuals with dark colour pattern achieve higher thoracic tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 67 publications
3
60
0
1
Order By: Relevance
“…The net effect of the cooler climate should make melanization an important fitnessrelated trait because it should benefit mate-finding opportunities in the Alps more compared with central Finland. Similarly, Punzalan et al [23] found that the thermoregulatory benefits of melanin increased fitness in the ambush bug (Phymata americana), but only when temperatures were at the lower limit of tolerance for the species. Although we did not directly link warm-up ability to fitness in our study, previous work on lepidopterans has shown fitness benefits of increased melanization [30][31][32]53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The net effect of the cooler climate should make melanization an important fitnessrelated trait because it should benefit mate-finding opportunities in the Alps more compared with central Finland. Similarly, Punzalan et al [23] found that the thermoregulatory benefits of melanin increased fitness in the ambush bug (Phymata americana), but only when temperatures were at the lower limit of tolerance for the species. Although we did not directly link warm-up ability to fitness in our study, previous work on lepidopterans has shown fitness benefits of increased melanization [30][31][32]53].…”
Section: Discussionmentioning
confidence: 99%
“…The use of dead moths allowed us to control for any differences in thermoregulationrelated behaviour, such as movement, repositioning of wings or differences in metabolic activity that might exist among differently melanized individuals. Previous studies have also used either dry [32] or fresh [23] dead individuals for similar reasons when exploring links between thermoregulation and coloration.…”
Section: (B) Thermal Property Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using dead moths we were able to control for any differences in thermoregulation-related behavior, which might exist among differently melanized individuals. At least two previous studies have also used either dry (Guppy 1986a) or freshly killed (Punzalan et al 2008) individuals for the same reason to look how coloration relates to thermoregulation.…”
Section: Thermoregulation (Ii)mentioning
confidence: 99%
“…Thermoregulation in many ectothermic species is important to fitness and benefitted by melanin (Pereboom & Biesmeijer 2003, Trullas et al 2007, Punzalan et al 2008. Melanin is a dark compound found in the coloration of many animals and is thought and shown to trade-off with other fitness-related traits (Talloen et al 2004, Lindstedt et al 2009).…”
Section: Trait Trade-offs and Interactionsmentioning
confidence: 99%